Xylose and Arabinose Fermentation to Produce Ethanol by Isolated Yeasts from Durian (Durio zibethinus L.) Fruit - Hermansyah Hermansyah; Fachrijal Fachrijal; Miksusanti Miksusanti; Fatma Fatma; Getari Kasmiarti; Almunadi T Panagan (Universitas Jenderal Soedirman, 2019)
Xylose and arabinose are pentosesugars that present in hemicellulose, part of lignocellulose biomass.These pentose sugars can be fermented by yeast into ethanol.The aim of this research was to utilize yeast isolated from durian fruit (DuriozibethinusL.) in fermentation of xylose and arabinose to produce bioethanol.Phenotypic test of isolates was conducted by growingthe isolates in various agar media, i.e.YPD (Yeast Peptone Dextrose), YPA (Yeast Peptone Arabinose), and YPX (Yeast Peptone Xylose) containing dextrose, arabinose, xylose, respectively, assole carbon source to see cell growth. The yeast isolates were further identified using API AOC 20C kit method. Yeast isolates were applied for fermentation of glucose, arabinose, and xylosein incubated cultures. Ethanol production in the fermentation was analyzed bygaschromatography. Yeast isolates were identified as Kodamaea ohmeri, Candida famata, Candida guilliermondii, and Crytococcuc laurentii. Based on gas chromatography data, it was found that ethanol produced in the fermentation for three days, the highest ethanol content on xylose substrate was fermented by Candida famata-Awhich is0.021% (v/v) ethanol resulted from initial concentration of 5% xylose (w/v). While on arabinose substrate, the highest ethanol content was fermented by Crytococcus laurentii-Bwhich is 0.0034% (v/v) ethanol resulted from initial concentration of 5% arabinose (w/v).